Strong winds and widow makers : workers, nature, and environmental conflict in Pacific Northwest timber country - Beda, Steven C., 1980- (Working class in American history., 2023)
"Often cast as villains in the Northwest's environmental battles, timber workers in fact have a connection to the forest that goes far beyond jobs and economic issues. Steven C. Beda explores the complex true story of how and why timber- working communities have concerned themselves with the health and future of the woods surrounding them. Life experiences like hunting, fishing, foraging, and hiking imbued timber country with meanings and values that nurtured a deep sense of place in workers, their families, and their communities. This sense of place in turn shaped ideas about protection that sometimes clashed with the views of environmentalists--or the desires of employers. Beda's sympathetic, in-depth look at the human beings whose lives are embedded in the woods helps us understand that timber communities fought not just to protect their livelihood, but because they saw the forest as a vital part of themselves"--